Animated Videos as an Islamic Educational Medium for Children: A Systematic Literature Review - Dwi A, Rahmadita; Jenuri; Zinal Arifin (International Journal of Post Axial: Futuristic Teaching and Learning, 2023)
Learning media can influence the enthusiasm and interest of students in learning. This study aims to conduct a literature review related to the effectiveness of animated videos as a medium of Islamic education for early childhood. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection is done by documenting all articles related to keywords. The articles used in this study were 34 national journal articles obtained from Google Scholar. Based on this research, it was found that animated video media was effectively used in learning because it was proven to increase students' interest and was easy to understand. In addition, animated videos match the characteristics of early childhood